A lightweight abstract machine for interaction nets - Hassan, Abubakar; Mackie, Ian; Sato, Shinya (Electronic Communications of the EASST, 2010)
We present a new abstract machine for interaction nets and demonstratethat an implementation based on the ideas is significantly more efficient than existing interaction net evaluators. The machine, which is founded on a chemical abstract machine formulation of interaction nets, is a simplification of a previous abstract machine for interaction nets. This machine, together with an implementation, is at the heart of current work on using interaction nets as a new foundation as an intermediate language for compiler technology.